Satellite magnetic field over the Nares Strait region - Langel, Robert A.; Thorning, Leif (Meddelelser om Grønland. Geoscience, 1982)
The general characteristics of the total field magnetic anomalies from satellite data over the region adjacent to Nares Strait are briefly described. The interpretation of satellite data is still at an early stage, but it is favoured that the regional anomalies in this region reflect variations in composition and/or structure in the lower crust related to the lnnuitian Ellesmere-Greenland mobile belt. An elongated negative anomaly occurs over Ellesmere Island parallel to the Innuitian mobile belt and to Nares Strait. This negative anomaly separates major magnetic highs over northern Greenland and the Alpha Ridge of the Canada Basin. The magnetic contrast is interpreted to represent either a change in the thickness of the Precambrian crust or apetrologic change brought about during the formation of the Innuitian mobile belt.